2022
DOI: 10.3389/fendo.2022.895507
|View full text |Cite
|
Sign up to set email alerts
|

Primary Congenital Hypothyroidism in Children Below 3 Years Old - Etiology and Treatment With Overtreatment and Undertreatment Risks, a 5-Year Single Centre Experience

Abstract: Worldwide neonatal screening for congenital hypothyroidism (CH) is a gold standard of active surveillance in newborns. Prompt diagnosis, subsequent timely treatment implementation, and proper dosage of levothyroxine (L-T4) are crucial for normal growth and development, especially of the central nervous system. However, overtreatment may have a potential negative impact on further neurodevelopment. We retrospectively analysed data of 99 newborns with CH diagnosis, referred to the Endocrinology Outpatient Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…A retrospective study of a Polish CH newborn screening program between 2017 and 2021 demonstrated that 51 (58%) out of 88 patients were optimally treated, while approximately 25% were overtreated. The authors of this study suggested that overtreatment may have occurred among those with transient or milder forms of hypothyroidism who did not require as much exogenous thyroid hormone [ 23 ]. A belief exists among some clinicians that overtreatment may be more acceptable than undertreatment, but overtreatment may be associated with inattention, hyperactivity, anxiety, and deficits in cognitive function [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of a Polish CH newborn screening program between 2017 and 2021 demonstrated that 51 (58%) out of 88 patients were optimally treated, while approximately 25% were overtreated. The authors of this study suggested that overtreatment may have occurred among those with transient or milder forms of hypothyroidism who did not require as much exogenous thyroid hormone [ 23 ]. A belief exists among some clinicians that overtreatment may be more acceptable than undertreatment, but overtreatment may be associated with inattention, hyperactivity, anxiety, and deficits in cognitive function [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormone deficiency during pregnancy, as well as its severity and duration, are determining factors in the formation and organization of the fetal brain (UCHIDA K.; SUZUKI M., 2021). In addition, some other risk factors include the baby's gender, premature birth, country of origin, health condition of the newborn and being small for gestational age (LIPSKA E. et al, 2022).…”
Section: Mechanisms Underlying Cognitive Changesmentioning
confidence: 99%
“…Thyroid dysgenesis, which encompasses agenesis, hypotrophy, hemiagenesis and ectopy of the thyroid gland, is responsible for more than 50% of cases. Other causes include thyroid dyshormonogenesis, which is caused by mutations in genes involved in the synthesis and metabolism of thyroid hormones (LIPSKA E. et al, 2022).…”
Section: Mechanisms Underlying Cognitive Changesmentioning
confidence: 99%
See 1 more Smart Citation